Optimal consumption and portfolio choice under ambiguity for a mean-reverting risk premium in complete markets - Hening Liu (The University of Manchester, Manchester Business School, 2011)
This paper explicitly solves, in closed form, the optimal consumption and port folio choice for an ambiguity averse investor in a Merton-type two assets economy where a risk premium follows a mean-reverting process. The investor's preferences are represented by the recursive multiple priors utility model developed by Chen and Epstein (2002). The investor's utility depends on both intermediate consumption and terminal wealth. Under the assumption of complete markets, I use the martingale method to solve the dynamic optimization problem in continuous time. I find that ambiguity can decrease the optimal consumption-to-wealth ratio, the intertemporal hedging demand and the optimal portfolio allocation, but magnifies the importance of hedging demand in the optimal portfolio allocation. In addition, ambiguity also increases riskless savings.
Keywords: G11; D81; C61; 330; Consumption; Portfolio Choice; Ambiguity; Risk Premium; Portfolio-Management; Risikoaversion; Martingale